The important role of cuproptosis and cuproptosis-related genes in the development of thyroid carcinoma revealed by transcriptomic analysis and experiments - Yani Liu; Yanyan He; Shizhen Lei (Brazilian Journal of Otorhinolaryngology)
Objective: Programmed Cell Death (PCD) processes have been suggested to play a role in the development of cancers. The study aimed to investigate the enrichment of different types of PCD and identify important PCD-related genes in Thyroid Carcinoma (THCA). Methods: The whole study is based on transcriptomic analysis and Immunohistochemistry (IHC) experiments. For transcriptomic analysis, the transcriptomic data of THCA (n = 493) and normal thyroid samples (n = 58) was used. The enrichment score of different types of PCD in THCA samples was calculated and the most enriched PCD process was identified. Then the expression of PCD-related genes in control and THCA samples were compared and the association between cuproptosis and characteristics of Tumor Microenvironment (TME) in THCA tissues was explored. IHC experiment was performed to confirm gene expressions in THCA and para-tumor samples. Results: Enrichment analysis showed that cuproptosis was the most enriched type of PCD process and associated with malignancy in THCA. The expression of a cuproptosis-related gene, CDKN2A, was found and confirmed to be higher in THCA than normal samples and associated with poor outcomes and higher clinical stages of patients with THCA. Moreover, CDKN2A expression was associated with immunosuppressive TME in THCA. Conclusion: Our findings indicated the important role of cuproptosis and a cuproptosis-related gene, CDKN2A, in the development and progression of THCA, which might provide novel insights into the understanding of pathophysiology of THCA.